Cytogenetic study for Iraqi patients with epilepsy: Cytogenetics of epilepsy patients - Asmaa Amer Almukhtar; Amal Mohammed Ali; Noor Hashim Ismail (Iraqi Journal of Cancer and Medical Genetics, 2023)
The current study was conducted with the aim of identifying the chromosomal changes that associated with epilepsy Iraqi patients. Chromosomal analysis was carried on for 37 of a number of epilepsy patients exclusively for cases of idiopathic epilepsy (unknown cause)after excluding the symptomatic epilepsy (known causes) range age from 2-51 years. Only five cases showed chromosomal changes associated with epilepsy cases, their ages ranged from 2-30 years, while the rest of the patients had normal karyotype. The chromosomes were prepared using the GTG band with average of 25-30 cells was examined for each person. The chromosomal changes that associated with epilepsy cases, ranged from the presence of a number of derivative chromosomes, inversion, additions, deletions, chromatid fractures, and the premature centromere division (PCD).Finally the recurrence of aberrations in some chromosomes (more than one defect associated with the same chromosome). Which may indicate that these chromosomes carry more than one fragile site sin same chromosome. During questionnaire there were other symptoms associated with epilepsy which has been mentioned to them in the study.